Estimating contrasting soil moisture-precipitation feedbacks across global landmass using data from the Soil Moisture Active Passive satellite mission - Joshua Taylor; Guido Salvucci (Science of Remote Sensing, 2025)
The effect of soil moisture on future precipitation is complex and has been the subject of significant research. Observational and modeling studies have been carried out on a variety of spatial (e.g., mesoscale to continental) and temporal (e.g., daily to monthly) timescales. Our methodology statistically measures the interaction between morning soil moisture and subsequent probability of precipitation using the Granger Causality approach, with global data from remotely sensed estimates of soil moisture from the Soil Moisture Active Passive (SMAP) and Advanced Microwave Scanning Radiometer 2 (AMSR2) instruments. The SMAP and AMSR2 results are compared, and found to be consistent with each other and with a previous analysis that applied a Granger Causality framework with data from the Advanced Microwave Scanning Radiometer for Earth Observing System (AMSR-E) over the conterminous U.S. We find that the impact of soil moisture on next day precipitation likelihood varies across the global landmass, with patterns related to overall aridity and land cover.